Operating Effectiveness Based on Good Governance Management of Local Government Organizations in Lopburi Province Affecting Public Policy According to the People’s Quality of Life - Kongsutjai, Santisak; Jongkatkorn, Chaowarit (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
The objectives of this research were to study 1) the level of effectivenss of the operation of the local government organization in Lopburi province; 2) the performance according to the good governance of the local governmant organization affecting the policy on the quality of life of the people in Lopburi province. and 3) To study the factors affecting the efficiency of the implementation of good governance of local administrative organizations in Lopburi Provice. The sample in the research were People in 126 local government organizations in Lopburi Province A sample of 400 people was obtaied. The qualitative research used a structured interview of 10 peopleUse quantitative and qualitative research methods. Analyzed by descriptive statistics and analyzed the relationship of the implementation of the good governance in 6 areas with the 5 areas by multiple regression analysis section uses internal content and consistency analysis techniqes. The result of study found that: Good governance management of Local Administrative Organization in Lop Buri had quality at high level, = 3.69, SD = 0.98. It found that the analysis result of good governance management influencing to the quality of people’s lives in overall was at high level, = 3.77, SD = 0.77. As the quality of people’s lives, the satisfaction for community activity participation was the highest: = 3.85, SD = 0.94, the next was life satisfaction: = 3.81, SD = 0.96, multiple regression analysis, and good governance management explaining the influence to the quality of people’s lives for 72.0% (R2=.720), the factor influencing to transparency, participation, accountability, and cost effectiveness were at higher level making the quality of people’s lives better. The result of qualitative research found that Local Administrative Organization still lacked of efficiency to follow policies, statute of limitations and official regulations. The point was lack of strengthening and the community participation for management examination.